The Illiterate Listener: On Music Cognition, Musicality and Methodology - Honing, Henkjan (Amsterdam University Press, 2011)
We have known for some time that babies possess a keen perceptual sensitivity for the melodic, rhythmic and dynamic aspects of speech and music: aspects that linguists are inclined to categorize under the term 'prosody', but which are in fact the building blocks of music. Only much later in a child's development does he make use of this 'musical prosody', for instance in delineating and subsequently recognizing word boundaries. In this essay Henkjan Honing makes a case for 'illiterate listening', the human ability to discern, interpret and appreciate musical nuances already from day one, long before a single word has been uttered, let alone conceived. It is the preverbal and preliterate stage that is dominated by musical listening.